2009
DOI: 10.1007/s10620-009-0986-y
|View full text |Cite
|
Sign up to set email alerts
|

JC Virus T-Antigen DNA in Gastrointestinal Mucosa of Immunosuppressed Patients: A Prospective, Controlled Study

Abstract: JCV T-Ag DNA is more prevalent in the upper and lower GI mucosa of immunosuppressed patients, possibly indicating that the virus resides in these patients. This may account for the higher prevalence of GI carcinomas in immunosuppressed patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Thus, JCV is a good candidate to be the missing link in familial CRC when obvious genetic explanation is missing. In previous studies, we demonstrated a correlation between positive serology to JCV and CRC or adenomatous polyps, as well as JCV DNA in the tumors in CRC Israeli patients and in the normal colonic mucosa of immunosuppressed patients [14][15][16]. In the present study, we found JCV T Ag in the tumor tissue or in adjacent normal mucosa in almost twice as many of the patients with a family history of CRC than in patients with no such family history.…”
Section: Discussionsupporting
confidence: 75%
“…Thus, JCV is a good candidate to be the missing link in familial CRC when obvious genetic explanation is missing. In previous studies, we demonstrated a correlation between positive serology to JCV and CRC or adenomatous polyps, as well as JCV DNA in the tumors in CRC Israeli patients and in the normal colonic mucosa of immunosuppressed patients [14][15][16]. In the present study, we found JCV T Ag in the tumor tissue or in adjacent normal mucosa in almost twice as many of the patients with a family history of CRC than in patients with no such family history.…”
Section: Discussionsupporting
confidence: 75%
“…JCV has been detected in stools or intestinal mucosa of healthy individuals and immunocompromised patients, including transplant recipients . The virus has also been isolated from glial cells of the myenteric plexus and has been implicated in development of chronic idiopathic intestinal pseudo‐obstruction .…”
Section: Discussionmentioning
confidence: 99%
“…As with BKV, JCV remains latent in the kidney and bone marrow after primary infection . The latent virus has also been detected in the upper and lower gastrointestinal mucosa of immunosuppressed patients . Reactivation of the virus can cause PML, a severe and often lethal demyelinating disease of the central nervous system .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have addressed the prevalence of JCPyV in tumors of immunosuppressed patients. In a recent study, Bolting et al observed a higher prevalence of JCPyV DNA in the normal mucosa of the gastrointestinal tracts of patients who received immunosuppressant therapy than in immunocompetent control individuals (23,7% vs. 6,3%; p = 0,02) 172 . Importantly, organ transplant recipients exhibited a relative risk of 10.4 (prevalence 35,3%) for carrying viral DNA.…”
Section: Introductionmentioning
confidence: 92%